2022
DOI: 10.3389/fpubh.2022.900751
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Alleviates Myocardial Injury in a Rat Model of Acute Myocardial Infarction Supported by Venoarterial Extracorporeal Membrane Oxygenation

Abstract: Myocardial ischemia causes myocardial inflammation. Research indicates that the venoarterial extracorporeal membrane oxygenation (VA ECMO) provides cardiac support; however, the inflammatory response caused by myocardial ischemia remains unresolved. Dexamethasone (Dex), a broad anti-inflammatory agent, exhibits a cardioprotective effect. This study aims to investigate the effect of Dex on a rat model of acute myocardial infarction (AMI) supported by VA ECMO. Male Sprague-Dawley rats (300–350 g) were randomly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Although this study did not investigate the exact inhibitory mechanisms of DEX and ramipril on the supravalvular aortic stenosis myocardial cytokine generation, our results confirm their significant anti-inflammatory effect, as shown by other studies [27,33,34,43,44,56]. The present study showed that myocardial levels of TNFα, IL1-α and IL-6 were lower after both treatments, DEX and ramipril compared to AS rats.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although this study did not investigate the exact inhibitory mechanisms of DEX and ramipril on the supravalvular aortic stenosis myocardial cytokine generation, our results confirm their significant anti-inflammatory effect, as shown by other studies [27,33,34,43,44,56]. The present study showed that myocardial levels of TNFα, IL1-α and IL-6 were lower after both treatments, DEX and ramipril compared to AS rats.…”
Section: Discussionsupporting
confidence: 85%
“…Dexamethasone (DEX), as well as other glucocorticoids, is known for its potent antiinflammatory effects, but there are some controversial results regarding its effects on cardiac remodeling and function [27,[29][30][31][32][33][34]. It has been shown that treatment with DEX is able to inhibit inflammatory cytokines, myocardial fibrosis and reactive oxygen species (ROS), resulting in an improvement in cardiac remodeling and cardiac function in an experimental protocol of CHF in rats induced by left coronary artery ligation [27,31,33,34]. In contrast, another study demonstrated that DEX treatment inhibited the regeneration and recovery of cardiac function in the heart of 2-day-old post-myocardium infarction pigs [32].…”
Section: Introductionmentioning
confidence: 99%